Layanan Konseling Kelompok Tekhnik Assertive Training dalam Menangani Konsep Diri Negatif pada Peserta Didik - Maharani, Laila; Ningsih, Tika (Universitas Islam Negeri Raden Intan Lampung, 2015)
The purpose of this research is to know whether counseling service of assertive training group can handle negative self concept in students of SMP Negeri 12 Bandar Lampung. The method used in this research is quasi experimental research with the design of One Group Pretest and Posttest Design. The sample in the study amounted to 12 students class IX SMPN 12 Bandar Lampung which has a negative self concept. Technique of collecting data in this research using self concept scale, interview, observation, and documentation. The results of data analysis indicate that there is an improvement in handling the negative self-concept of learners before and after being given group counseling services with assertive training techniques on learners.